STAGE DISTRIBUTION AND PATIENT RESPONSE POST NEO-ADJUVANT SHORT COURSE RADIOTHERAPY IN RECTAL CANCER, SINGLE CENTER STUDY - Mohammed, Kamaran Ahmed; Ghalib, Hawar Hasan Ali (Journal of Sulaimani Medical College, 2019)
Background Colorectal cancer (CRC) is one of the leading causes of mortality and morbidity in the world. It is the third most common malignancy and the fourth leading cause of cancer-related deaths worldwide, accounting for approximately 1,400,000 new cases and about 700,000 deaths worldwide. Objectives The objective of this study is to assess patients’ response and developments of complication, after the use of neo-adjuvant short course radiotherapy in addition to the effect of this treatment modality on pathological response, local control and distant metastasis. Methods Forty six patients, who were histopathologically proven to have colorectal carcinoma, were randomly assigned to receive 25 Gy of radiation, in a short period of time prior to surgical resection of tumor. Local control, distance metastasis and post operative signs and symptoms measured over a period of 5 years (2013-2018). The treatment period ranged between 3-327 days. Results The overall survival of patients and their experience with post operative toxicity was improved; there was statistically significant correlation between spread of the tumor and duration of radiotherapy, p value was less than 0.05.In addition 84% of cases had no recurrence. Overall survival was about 76% of cases at the end of this research. The rate of post operative complication decreased. But the duration of radiotherapy had no significant effect on the mortality. (p value=0.2) Conclusion Preoperative short-course radiotherapy before colorectal surgical intervention favors better local control and distant metastasis in addition to less complication, more comfort for patients and favorable survival rate.
Keywords: Neo-adjuvant Short Course Radiotherapy; Rectal Cancer